Disregulasi Respon Imun pada Kanker Payudara: Tinjauan Epidemiologi, Subtipe Molekuler, dan Terapi - Maula Syakira; Nisa Ulmafhigrah; Firdus Firdus; Rosnizar Rosnizar (INDO PUBLISHING, 2026)
Breast cancer is the disease with the highest mortality rate in women worldwide. Breast cancer development is influenced not only by the intrinsic characteristics of tumor cells but also by the complex interactions between cancer cells, the immune system, and components of the tumor microenvironment (TME). Dysregulation of the immune response plays a crucial role in disease progression through various mechanisms, including immunosuppression, immune evasion, and altered immune cell function. This article aims to comprehensively examine the mechanisms of immune response dysregulation in breast cancer based on the latest scientific literature. The method used is a literature review by reviewing various relevant research articles and review articles regarding breast cancer molecular subtypes, TME characteristics, the role of immune cells, and factors influencing the immune response in breast cancer. The results of this study indicate that breast cancer molecular subtypes have distinct immunological characteristics that influence disease progression and therapeutic response. A deeper understanding of these mechanisms is expected to support the development of more effective therapeutic strategies, particularly immunotherapy tailored to the patient's biological characteristics.